2017
DOI: 10.1148/radiol.2017161177
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis: Data-driven Textural Analysis of Extent of Fibrosis at Baseline and 15-Month Follow-up

Abstract: Purpose To evaluate associations between pulmonary function and both quantitative analysis and visual assessment of thin-section computed tomography (CT) images at baseline and at 15-month follow-up in subjects with idiopathic pulmonary fibrosis (IPF). Materials and Methods This retrospective analysis of preexisting anonymized data, collected prospectively between 2007 and 2013 in a HIPAA-compliant study, was exempt from additional institutional review board approval. The extent of lung fibrosis at baseline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 27 publications
(26 reference statements)
2
91
0
Order By: Relevance
“…In nearly all cases, high-resolution computed tomography (HRCT) is the primary tool for diagnosis [5]. HRCT (in particular, the fibrosis score) can also help determine the prognosis in ILDs, and quantitative computed tomography (CT) analysis may be useful for evaluating disease progression [17][18][19] (the article by WALSH et al [20] in this issue of the European Respiratory Review provides more detail on imaging in fibrosing ILDs that may present a progressive phenotype). ILD diagnoses should be categorised as confident, provisional or unclassifiable depending on the level of diagnostic confidence.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…In nearly all cases, high-resolution computed tomography (HRCT) is the primary tool for diagnosis [5]. HRCT (in particular, the fibrosis score) can also help determine the prognosis in ILDs, and quantitative computed tomography (CT) analysis may be useful for evaluating disease progression [17][18][19] (the article by WALSH et al [20] in this issue of the European Respiratory Review provides more detail on imaging in fibrosing ILDs that may present a progressive phenotype). ILD diagnoses should be categorised as confident, provisional or unclassifiable depending on the level of diagnostic confidence.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…In chess, ML is valuable in any setting that will benefit from efficiently detecting patterns in complex data. In radiology, for example, ML has been used to predict genetic variations in low-grade gliomas (4), to identify genetic phenotypes in small-cell lung carcinoma (5), to decrease false-positive results in screening mammography CAD (6), to improve pathologic mediastinal lymph node detection (7), to automatically perform bone age assessment (8), and to quantify lung fibrosis on computed tomographic (CT) images (9).…”
Section: Machine Versus Human or Machine Plus Human?mentioning
confidence: 99%
“…For example, in interstitial lung disease, early signs of disease which manifest as interstitial lung abnormalities (ILA) on chest CT scans have been associated with numerous risk factors for disease . A recent clinical study also concluded that changes in CT texture measures are significantly correlated with changes of pulmonary function in patients with idiopathic pulmonary fibrosis, and can be used to predict diminished function in these patients . Therefore, a detailed view of such features would allow for earlier diagnoses, faster determination and better monitoring of treatment.…”
Section: Introductionmentioning
confidence: 99%